The evaluation of the incidence of sensorineural component of hearing loss in chronic suppurative otitis media - Jha, Shruti; Singh, Rakesh Kumar (International Journal of Research in Medical Sciences, 2022)
Background: The sensorineural component of hearing loss either in form of pure sensorineural or Mixed components has since long been suspected to be a dreaded sequela of chronic suppurative otitis media (CSOM). The aim of this study is to access the incidence of sensorineural hearing loss (SNHL) or mixed hearing loss (MHL) amongst people suffering from both mucosal and squamosal variants of CSOM. Methods: A prospective observational cohort study (control group: contralateral ear) was conducted at the E.N.T. department of tertiary care center from December 2020 to September 2022. 149 patients of ages 15-50 of either gender with unilateral CSOM were included in the study. The other normal ear of the same patient was taken as the control ear. The pure tone audiometry of both diseased and control ears at frequencies 500,1000,2000 and 4000 kHz were taken to determine SNHL or MHL. Results: The mean age was 26.54±8.75 years of which, 79 males and 70 females. The mean duration of disease was 3.92±3.32. SNHL occurred in 25.5% of cases, while conductive and MHL affected 69.8% and 4.7 % of patients respectively. Conclusions: SNHL and MHL occurred in a significant number of patients suffering from CSOM. Further research needs to be encouraged and management should be refined to decrease disease-related morbidity.